Digestibility of pre-treated cassava peel as feed ingredient for Nile tilapia - Mulyasari; Kurniawati, Feri; Setiawati, Mia (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT This research aimed at determining digestibility coefficient of cassava peel(Manihot utilissima) after immersion in 3% (w/v) NaOH for three days, fermentation using combined fungi of 10% Trichoderma viride and Phanerochaete chrysosporium for seven days, and fermentation using 15% (w/w) Bacillus megaterium for five days as feed ingredients for Nile tilapia Oreochromis niloticus. Total digestibility test was conducted by mixing 30% of cassava peel and 70% of reference diet. Nile tilapia at the average weight of 16.6 g were used as experimental fish. Fish was held for 28 days in aquarium (50x50x50 cm3) at the density of 10 fish/aquarium. Fish were fed twice daily to satiation. Feces collection started after five days of adaptation to chromium oxide diets. The results showed that the three treatments had significant effects compared to control (P<0.05), protein digestibility of were improved 5%, 15%, and 10%, energy digestibilitiy were 20%, 18%, 16%, and total digestibility of test cassava peel were 174%, 151%, and 164%, respectively. Cassava peel fermented with combined 10% mold showed the highest protein digestibility impliying it potency as feed ingredient for Nile tilapia diet. Keywords: Nile tilapia, cassava peel, NaOH, mold, bacteria, digestibility  ABSTRAK Penelitian ini bertujuan untuk mengevaluasi kecernaan kulit ubi kayu (Manihot utilissima) setelah perendaman dengan NaOH 3% (w/v) selama tiga hari, fermentasi kapang Trichoderma viride dan Phanerochaete chrysosporium 10% (w/w) selama tujuh hari, dan fermentasi bakteri Bacillus megaterium 15% (w/w) selama lima hari sebagai bahan baku pakan ikan nila. Uji kecernaan total bahan dilakukan dengan mencampurkan 30% kulit ubi kayu dengan 70% pakan acuan. Ikan uji yang digunakan adalah ikan nila dengan bobot rata-rata 16,6 g. Ikan dipelihara selama 28 hari dengan kepadatan 10 ekor/akuarium berukuran 50x50x50 cm3. Pemberian pakan dilakukan dua kali sehari secara at satiation. Pengumpulan feses dimulai setelah lima hari adaptasi pakan uji yang diberi indikator kromium oksida. Hasil penelitian menunjukkan bahwa ketiga perlakuan memberikan pengaruh yang berbeda nyata terhadap kontrol (P<0,05) dan meningkatkan nilai kecernaan protein pakan berturut-turut sebesar 5%, 15%, dan 10%, nilai kecernaan energi sebesar 20%, 18%, dan 16%, serta nilai kecernaan total bahan sebesar 174%, 151%, dan 164%. Perlakuan kulit ubi kayu yang difermentasi dengan kapang menunjukkan nilai kecernaan protein pakan yang tertinggi sehingga berpotensi sebagai bahan baku pakan ikan nila. Kata kunci: ikan nila, kulit ubi kayu, NaOH, kapang, bakteri, kecernaan